Feminization of Agriculture in the Context of Rural Transformations : What is the Evidence? - Slavchevska, Vanya; Kaaria, Susan; Taivalmaa, Sanna-Liisa (World Bank, Washington, DC, 2016)
Male outmigration, the globalization of agri-food systems, conflict, and pandemic human disease have all been linked to changes in rural economies, changes in women’s roles in the agricultural sector, and consequently to assertions that agriculture is “feminizing.” This review assesses the global evidence surrounding the feminization of agriculture. First, it proposes a number of indicators to track the feminization of agriculture, noting that although limited data exist for some of the indicators, efforts should be expanded to collect data for all of them to provide better diagnostics of women’s work in agriculture and their welfare. Next, it critically examines the factors that may lead to the feminization of agriculture and evaluates the empirical evidence on each factor worldwide. The review concludes by identifying policy imperatives based on the evidence on women’s roles in agriculture in the context of rural transformation